“Oxygen Sensing” by Na,K-ATPase: These Miraculous Thiols - Bogdanova, Anna; Petrushanko, Irina Y.; Hernansanz-Agustín, Pablo; Martínez-Ruiz, Antonio (Frontiers in Physiology, 2016)
Control over the Na,K-ATPase function plays a central role in adaptation of the organisms to hypoxic and anoxic conditions. As the enzyme itself does not possess O2 binding sites its “oxygen-sensitivity” is mediated by a variety of redox-sensitive modifications including S-glutathionylation, S-nitrosylation and redox-sensitive phosphorylation. This is an overview of the current knowledge on the plethora of molecular mechanisms tuning the activity of the ATP-consuming Na,K-ATPase to the cellular metabolic activity. Recent findings suggest that oxygen-derived free radicals and H2O2, NO, and oxidised glutathione are the signalling messengers that make the Na,K-ATPase “oxygen-sensitive”. This very ancient signalling pathway targeting thiols of all three subunits of the Na,K-ATPase as well as redox-sensitive kinases sustains the enzyme activity at the “optimal” level avoiding terminal ATP depletion and maintaining the transmembrane ion gradients in cells of anoxia-tolerant species. We acknowledge the complexity of the underlying processes as we characterise the sources of reactive oxygen and nitrogen species production in hypoxic cells, and identify their targets, the reactive thiol groups which, upon modification, impact the enzyme activity. Structured accordingly, this review presents a summery on (i) the sources of free radical production in hypoxic cells, (ii) localisation of regulatory thiols within the Na,K-ATPase and the role reversible thiol modifications play in responses of the enzymes to a variety of stimuli (hypoxia, receptors’ activation) control of the enzyme activity (iii) redox-sensitive regulatory phosphorylation, and (iv) the role of fine modulation of the Na,K-ATPase function in survival success under hypoxic conditions. The co-authors attempted to cover all the contradictions and standing hypotheses in the field and propose the possible future developments in this dynamic area of research, the importance of which is hard to overestimate. Better understanding of the processes underlying successful adaptation strategies will make it possible to harness them and use for treatment of patients with stroke and myocardial infarction, sleep apnoea and high altitude pulmonary oedema, and those undergoing surgical interventions associated with the interruption of blood perfusion.